Ionic compatibilization of polypropylene/polyamide 6 blends using an ionic liquids/nanotalc filler combination: morphology, thermal and mechanical properties. Issue 57 (25th June 2015) - Yousfi, M.; Livi, S.; Dumas, A.; Crépin-Leblond, J.; Greenhill-Hooper, M.; Duchet-Rumeau, J.
<x xml:space="preserve">Abstract</x> In this study, room temperature ionic liquids (RTILs) based on phosphonium cations have been used as effective compatibilizers of polyolefin/polyamide 6/synthetic talc blends using a melt extrusion process.